2016
DOI: 10.1002/2016jc012337
|View full text |Cite
|
Sign up to set email alerts
|

Gulf of Maine salinity variation and its correlation with upstream Scotian Shelf currents at seasonal and interannual time scales

Abstract: In the Gulf of Maine (GoM), a network of buoy hydrography measurements collected since 2001 provide a subsurface salinity time series showing a strong seasonal cycle and interannual variations that are both consistent with remote forcing of Gulf hydrography by upstream advection. These long‐term mooring data are combined with satellite altimeter estimates of upper ocean current anomaly on the adjoining Scotian Shelf (SS) in a new attempt to use disparate regional observations as proxies to detect and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 53 publications
3
51
0
Order By: Relevance
“…On the other hand, the coastal current can be influenced by offshore pressure forcing, particularly in the vicinity of the WBCs (Archer et al, 2017;Csanady, 1978;Kelly & Chapman, 1988;Liu et al, 2016;Xu & Oey, 2011). It has been suggested that interannual variations in the alongshore current near the coast are related to remote wind forcing (Bachèlery et al, 2016), cross-shore wind stress curl gradient (Davis & Di Lorenzo, 2015), and alongshore (Li et al, 2014) and cross-shore (Feng et al, 2016) wind stress.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the coastal current can be influenced by offshore pressure forcing, particularly in the vicinity of the WBCs (Archer et al, 2017;Csanady, 1978;Kelly & Chapman, 1988;Liu et al, 2016;Xu & Oey, 2011). It has been suggested that interannual variations in the alongshore current near the coast are related to remote wind forcing (Bachèlery et al, 2016), cross-shore wind stress curl gradient (Davis & Di Lorenzo, 2015), and alongshore (Li et al, 2014) and cross-shore (Feng et al, 2016) wind stress.…”
Section: Introductionmentioning
confidence: 99%
“…Sea level variations [Ezer and Atkinson, 2014], Gulf Stream position shifts [Andres, 2016], and a high recent rate in upper ocean heating [Gawarkiewicz et al, 2012;Mills et al, 2013] are all observed, with differing potential impacts on the circulation, ecosystems, and coastal populations. Regional salinity change is also under study [Townsend et al, 2015;Li et al, 2014;Feng et al, 2016], mainly using in situ observations, with ecosystem implications tied to changing nutrients and factors controlling ocean acidification rates. These studies identify the need for spatially resolved and shelf-wide salinity observations.…”
Section: Introductionmentioning
confidence: 99%
“…It is transported southwestward down the coast within the Scotian Shelf Current (SSC, inshore branch). The variability of this coastal transport is an important factor controlling freshwater inflows into the GoM (Feng et al [3]). To assess this as a possible explanation for the observed SMAP SSSA data near buoys N01 and M01, we present climatological and anomalous ocean current and wind data for October and November 2016 in Figure 15.…”
Section: Applying Smap Data To Gulf Of Maine Sss Monitoringmentioning
confidence: 99%
“…The primary inflow to the GoM is through The dominance of subsurface GoM exchange pathways has, so far, limited the utility of surface remote sensing data for monitoring GoM dynamics. However, Feng et al [3] recently used altimeter data to demonstrate that seasonal and interannual variability in near-surface freshwater advection from the Scotian Shelf into the coastal GoM can be related to local wind-induced changes in the remote upstream coastal geostrophic currents. That study, amongst others cited, highlighted the need to resolve spatial information on surface salinity fields just offshore of and inside the GoM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation